Constructed wetland substrates: A review on development, function mechanisms, and application in contaminants removal. (January 2022) - Ji, Zehua; Tang, Wenzhong; Pei, Yuansheng
Abstract: Constructed wetlands (CWs) are economical, efficient, and sustainable wastewater treatment method. Substrates in CWs inextricably link with the other key components and significantly influence the performance and sustainability of CWs. Gradually, CWs have been applied to treat more complex contaminants from different fields, thus has brought forward new demand on substrates for enhancing the performance and sustainability of CWs. Various materials have been used as substrates in CWs, and their individual characteristics and application advantages have been extensively studied in recent years. Therefore, this review summarizes the development, function mechanisms (e.g., filtration, adsorption, electron supply, supporting plant growth and microbial reproduction), categories, and applications of substrates in CWs. The interaction mechanisms of substrates with contaminants/plants/microorganisms are comprehensively described, and the characteristics and advantages of different substrate categories (e.g., Natural mineral materials, chemical products, biomass materials, industrial and municipal by-products, modified functional materials, and novel materials) are critically evaluated. Meanwhile, the influences of substrate layer arrangement and synergism on contaminants removal are firstly systematically reviewed. Furthermore, further research about substrates (e.g., clogging, life cycle assessment/management, internal relationship between components) should be systematically carried out for improving efficiency and sustainability of CWs. Graphical abstract: Image 1 Highlights: Detailedly reviewed interaction mechanisms of substrates with contaminants/plants/microorganisms. Critically evaluated the individual characteristics and advantages of substrates. Systematically reviewed the substrate arrangement/synergism.